Electron butterfly distributions at particular magnetic latitudes observed during Juno's perijove pass. Issue 10 (25th May 2017) - Ma, Q.; Thorne, R. M.; Li, W.; Zhang, X.‐J.; Mauk, B. H.; Paranicas, C.; Haggerty, D. K.; Kurth, W. S.; Connerney, J. E. P.; Bagenal, F.; Bolton, S. J.
Abstract: We report observations of energetic electron butterfly distributions measured in a narrow range of Jupiter's magnetic latitudes by Juno during perijove 1. The electron butterfly distributions are characterized as clear electron flux peaks at 30–80° pitch angles, compared with the 90°‐peaked pitch angle distributions of the trapped electrons. Jupiter Energetic Particle Detector Instrument measurements during the close approach to Jupiter indicate a specific electron population with butterfly distributions formed between the main auroral oval and the radiation belt. The off‐90° flux peak is most clearly observed at tens of keV energies and gradually merges toward 90° pitch angle at higher energies. By projecting the observed electron pitch angle distributions along the magnetic field line, we found that the electron butterfly distributions are observed close to their source region. The particular electron distribution is possibly formed by parallel acceleration of electrons through Landau resonance with electrostatic waves. Key Points: Juno observed electron butterfly‐shaped pitch angle distributions between the main auroral oval and the radiation belt The electron butterfly distributions were locally produced through nonadiabatic processes or observed close to their source regions Landau resonant interactions between the electrons and electrostatic waves may cause the energy‐dependent electron butterfly distributions